NATURE OF GOOD-PARENT BELIEFS OF PARENTS OF CHILDREN SERVED BY A PEDIATRIC COMPLEX CARE PROGRAM - (:unkn) unknown (My University, 2025)
Good-parent beliefs, one’s idea of what it means to be a “good parent” to their child, function to help guide parental decision-making and facilitate coping in the context of pediatric illness. Among parents of children with advanced cancer and other complex illnesses, mixed-methods research has identified common themes across individuals’ good-parent beliefs. However, the good-parent beliefs of primary caregivers of children served by Complex Care Programs (CCPs) have not yet been explored. CCPs serve children with medical complexity (CMC), a distinct group of pediatric patients with multiple complex chronic medical illnesses and intensive medical involvement. Due to the chronicity and complexity of their conditions, parental medical decision-making for these children, and parent coping, are unique from other pediatric populations. This study aimed to describe the good-parent beliefs of primary caregivers of children served by CCPs and describe how these programs can best provide care in a way that aligns with parents’ good-parent beliefs. The current study included 15 primary caregivers of children served by a CCP at a large midwestern academic medical center. Qualitative interviews were conducted and analyzed using thematic analysis. All participants were able to describe their good-parent beliefs, and there were 16 good-parent beliefs identified in the sample. Good-parent beliefs were associated with medication- and surgery-related decision-making. They often provided direction to parents in managing their child’s complex needs, but they also served to incite rumination, identity challenges, and self-judgement for some. Despite not discussing good-parent beliefs directly with CCP staff, most participants felt that providers both understood their good-parent beliefs and acted in ways that helped parents to feel like a “good parent.” While many good-parent beliefs in the present study reflect those identified in other pediatric parent populations, current results suggest additional beliefs which have a focus on children’s growth and development, and on parent/caregiver well-being, as part of the role of being a “good parent” of CMC. Clinical implications are numerous for both pediatric medical and psychosocial providers, including the possibility of future development of population-specific psychotherapeutic interventions for caregivers. Future research is needed to elucidate the nature of good-parent beliefs more fully in this population, understand their functions, and guide clinicians to work most effectively with these families.
Keywords: Clinical psychology; children with medical complexity; good-parent beliefs; pediatric complex care